Peran Guru dalam Mengembangkan Kurikulum Merdeka di Madrasah Ibtidaiyah: Tantangan dan Strategi - Muhammad Nasir (PT. Global Pustaka Ilmiah, 2025)
Teachers have an important role in developing and implementing the independent curriculum in schools. However, due to lack of training, many teachers do not understand the concept of the independent curriculum. So it is very important for teachers to understand their role and the challenges in implementing the independent curriculum and strategies in overcoming these challenges. Therefore, this study aims to analyze and describe the challenges and strategies to overcome the challenges in implementing the independent curriculum effectively. This study uses descriptive literature. After collecting some data, the researcher analyzed it by connecting it to each other and then describing it. The results of the study show that teachers participate in developing the curriculum by adjusting learning materials and learning methods to the needs and characteristics of students. They are also responsible for creating relevant, innovative, and consistent learning materials, developing students' potential and interests. There are several challenges in the independent curriculum, such as lack of understanding of it, lack of teacher understanding of the learning model, limited resources and facilities, and lack of cooperation and discussion with parents and other parties involved. The strategy to overcome these challenges is to increase understanding of the independent curriculum, master various flexible teaching methods, utilize technology, communicate and collaborate with parents of students and other parties involved. So that the independent curriculum can be developed and implemented effectively.